Formation of the embryonic organizer is restricted by the competitive influences of Fgf signaling and the SoxB1 transcription factors - Kuo, Cheng-Liang; Lam, Chi Man; Hewitt, Jane E.; Scotting, Paul J. (Public Library of Science, 2013)
The organizer is one of the earliest structures to be established during vertebrate development and is crucial to subsequent patterning of the embryo. We have previously shown that the SoxB1 transcription factor, Sox3, plays a central role as a transcriptional repressor of zebrafish organizer gene expression. Recent data suggest that Fgf signaling has a positive influence on organizer formation, but its role remains to be fully elucidated. In order to better understand how Fgf signaling fits into the complex regulatory network that determines when and where the organizer forms, the relationship between the positive effects of Fgf signaling and the repressive effects of the SoxB1 factors must be resolved. This study demonstrates that both fgf3 and fgf8 are required for expression of the organizer genes, gsc and chd, and that SoxB1 factors (Sox3, and the zebrafish specific factors, Sox19a and Sox19b) can repress the expression of both fgf3 and fgf8. However, we also find that these SoxB1 factors inhibit the expression of gsc and chd independently of their repression of fgf expression. We show that ectopic expression of organizer genes induced solely by the inhibition of SoxB1 function is dependent upon the activation of fgf expression. These data allow us to describe a comprehensive signaling network in which the SoxB1 factors restrict organizer formation by inhibiting Fgf, Nodal and Wnt signaling, as well as independently repressing the targets of that signaling. The organizer therefore forms only where Nodal-induced Fgf signaling overlaps with Wnt signaling and the SoxB1 proteins are absent.